Foreword - Valantiejus, Algimantas (Sociologija. Mintis ir veiksmas, 1999)
The articles published in this issue of the journal are devoted to the sociology of history and the history of sociology. A use of such an expression is aimed to note two interrelated issues: first, the historically contextual link between the human action and the social experience; second, the structure of social forms, whose change is connected with the change of values, norms and ideals. To put it simply, the most important task of the social sciences is the attentiveness to the historicity.